Forest litter assessment in different age stands of rehabilitated forest in Bintulu, Sarawak, Malaysia - Kin, Melvin Ku Kin (2012)
Forest degradation caused by mankind disrupts the availability of natural resources of economic, environmental, social and cultural importance. Rehabilitation has the potential to improve degraded sites and restore the ecological processes. Thus, research is needed to enhance the understanding of ecological process development after rehabilitation. The objectives of this study were to estimate the production, decomposition and quality of forest litter in rehabilitated forests at Bintulu, Sarawak. Study plots of 20 m x 20 m were established in seven rehabilitated forest plots, P20 (20 years old, planted in 1991), P18 (18 years old, planted in 1993), P15 (15 years old), P12 (12 years old, planted in 1999), P9 (9 years old, planted in 2002), P6 (6 years old, planted in 2005), P3 (3 years old, planted in 2008), and PSF, an adjacent secondary forest. Litter production and decomposition was monitored in 4 plots, P20, P18, P12 and PSF. Using 1 m x 1 m litter traps placed randomly in the plot, litter fall was collected biweekly for 6 months and weighed after oven-drying. Litter decomposition was determined by using 80 litter bags placed randomly in the plot (2 mm mesh) filled with fresh fallen litter and was retrieved weekly for sorting and weighing. Standing crop litter was sampled from all 8 plots, where litter of 1 m2 area was carefully brushed, oven dried, weighed and then processed for litter quality analysis using standard procedures. The estimated mean annual litter production of P20, P18, P12 and PSF was 6.81 t ha-1 year-1, 3.09 t ha-1 year-1, 2.40 t ha-1 year-1 and 3.57 t ha-1 year-1 respectively. By litter component, leaf was highest followed by branches and others. Litter decomposition monitored revealed the decomposition followed the singleexponential model. The constant value (k) for litter decomposing in PSF has the lowest with 0.208 followed by both P12 and P18 at 0.216 while highest was P20 with 0.224. Standing crop litter of the older rehabilitated plots was significantly different compared to the younger plots. P20 recorded 18.26 t ha-1, P18 with 11.29 t ha-1, PSF with 7.45 t ha-1 and P6 and P3 at 5.25 t ha-1 and 4.52 t ha-1 respectively. However, standing crop litter in P15, P12 and P9 were not significantly different by statistical treatment. Standing crop litter was found to be acidic with pH ranging from 4.4 to 5.1 when measured in water, with significant differences among different stand ages. Concentration of nutrients in litter were categorically in the order of C>N>Ca>K>Mg>P irrespective of plots, generally with older plots having higher concentration of nutrients. Nitrogen ranged from 0.59 mg g-1 to 1.05 mg g-1, phosphorus 0.05 mg g-1 to 0.20 mg g-1, potassium 0.91 mg g-1 to 3.11 mg g-1, calcium 0.31 mg g-1 to 7.92 mg g-1 and magnesium 0.39 mg g-1 to 1.64 mg g-1. The results of production, decomposition and quality of forest litter followed a trend where ecological process rates increase with stand age. Data of rehabilitated forest showed similarity to that of other tropical forests, suggesting that rehabilitation is beneficial importance on ecological processes.